Addressing some of the challenges of cave mining - Jakubec, J. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Cave mining methods have been used in various forms for more than 100 years. Since their introduction, mining engineers and practitioners have strived to improve the method’s safety, economics, efficiency, and effectiveness. Over this period, thanks to developments in new technologies for extracting ore, as well as for predicting and monitoring mine performance, we have achieved higher production rates while venturing deeper and into more difficult conditions. However, this journey has not been entirely smooth. In fact, when critically assessing the outcomes of individual operations, most have fallen somewhat short of expectations in one way or another. The author of this paper reflects on the past 40 years and discusses some of the reasons for these shortfalls from the perspective of ‘caving rules’ and past experiences. It also examines today’s diverging thinking and opposing views on mine design and caving processes.